The relationship between ethics and Fiqh from the perspective of Allameh Javadi Amoli; Criticism and Study of the Theory of Ethics-Based Fiqh - Morteza Zamiri; Mostafa Zamiri; Hamidreza Aali (اخلاق وحیانی)
Discovering the relationship between the sciences of ethics and jurisprudence creates the basis for the correct classification of the two and the exploitation of each. Allamah Javadi Amoli is one of the thinkers who has explained the relationship between these two sciences in his works and has identified their commonalities and differences. Ethics and jurisprudence share the following characteristics: being organic, being included in practical wisdom, being sources of reference, and having five rulings, but they differ in the subject, rank, purpose, and quantity of issues. In this study, it is clear that the distinction in subject and rank has caused the propositions of the science of ethics to take precedence over the science of jurisprudence, in such a way that attention should be paid to the influence of jurisprudence on definitive moral propositions; whereas: 1) Man, by acting on religious duties, achieves the goal of acting on moral propositions. 2) Moral knowledge, in its absolute form, does not have enough definitive rational propositions to be a criterion for measuring the accuracy of jurisprudential propositions. 3) The knowledge of ethics does not mean moral propositions of the type of beliefs and therefore does not underlie jurisprudence. The aim of the present research is to recognize the relationship between ethics and jurisprudence in order to produce ethics-based jurisprudence and criticize it. The research method is analytical-critical and uses library resources.